Estimating the Relationship Between Special Education De-Identification for Emotional Disturbance and Academic and School Discipline Outcomes: Evidence From Wisconsin's Longitudinal Data. Issue 1 (January 2021) - Curran, F. Chris; Bal, Aydin; Goff, Peter; Mitchell, Nicholas
Students placed in special education programs for emotional and behavioral disorders with emotional disturbance (ED) identification have academic outcomes that lag both students in regular and special education. This issue is especially important for youth attending urban schools. Although prior research has examined students identified as ED, little research has examined how students who experience de-identification fare with regard to academic or behavioral outcomes. To our knowledge, this is the first study to examine the relationship between ED de-identification and student outcomes in the United States. The study uses longitudinal, administrative data to estimate the relationship between special education de-identification from ED and both academic and school discipline outcomes. Results of regression models with a variety of fixed effects, including student fixed effects, suggest that students who are de-identified have higher academic achievement after de-identification and a lower probability of experiencing an in-school suspension (ISS). Results for out-of-school suspension (OSS) are mixed. The results suggest that appropriately timed exit from special education services for students with ED who have been determined by individualized education program (IEP) teams to be suitable for de-identification is unlikely to harm students academically but that extra attention to OSS may be needed. The results point to the need for more attention to de-identification.